Geotechnical performance using alkaline activated fly ash for soil mixtures with and without polypropylene fibers - Rajeb Elkhebu, Ahmed Giuma (2018)
Soil stabilization is one of the well-known methods to treat problematic soils. Its advantages over soil replacement are that of low cost and fast implementation. Alkaline activation (geopolymerezation) of soft soils is a new technique that has been addressed recently to stabilize soft soils. Though it’s strengthening mechanism and final product in terms of stiffness and brittleness resembles that observed by cemented soils. In other words, the residual strength emerged when approaching failure is very low resulting in immediate damage of building structures. Therefore, the aforesaid shortcoming needs to be overcome particularly when horizontal displacement is present. In this regard, Potassium hydroxide was added to a mix of fly ash class F and polypropylene fibers to stabilize and reinforce Kaolin clay (S1) and marine clay (S2) respectively. The fly ash solid ratio was considered to be 10%, 20%, 30%, 40%, while polypropylene fiber proportions adapted for the study were 0.5%, 0.75%, 1% 1.25%. Compressive-, flexural- and indirect tensile tests as well as California bearing capacity (CBR)- & one dimensional consolidation tests were conducted. The compressive strength results of 28 days curing regime confirm the 40% fly ash mixture to contribute to the sharpest increase in compressive strength at 3680, 6980 kPa respectively. Though a sharp drop was observed. With the inclusion of polypropylene fibers, the mode of failure changed to a more ductile one resulting in peak strength values at 6450 kPa and 5834 kPa respectively. Besides, flexural and indirect tensile results were recorded to be 1555, 1770, 1833, 1819, 1541, 1777, 1545 and 1440 kPa for S1F40, S1FR0.75, S2F40 and S2FR0.75 respectively. In addition, the incorporation of fly ash and polypropylene fibers increased the CBR values of all pretreated mixtures indicating values of 51.2%, 69.8%, 48.1% and 59% for S1F40, S1FR0.75, S2F40 and S2FR0.75 respectively. Finally, the compression index and the preconsolidation pressure exhibited a substantial decrease and increase at 0.043, 0.076, 0.047, 0.104 and 900 kPa, 400 kPa, 500 kPa, 240 kPa for S1F40, S1FR0.75, S2F40 and S2FR0.75 respectively. It is to conclude, that the proposed new technique has a promising future to be used in soil stabilization domain where horizontal displacement is expected.